Monolignol export by diffusion down a polymerization-induced concentration gradient. Issue 5 (15th February 2022) - Perkins, Mendel L; Schuetz, Mathias; Unda, Faride; Chen, Kent T; Bally, Marcel B; Kulkarni, Jayesh A; Yan, Yifan; Pico, Joana; Castellarin, Simone D; Mansfield, Shawn D; Samuels, A Lacey
Abstract: Lignin, the second most abundant biopolymer, is a promising renewable energy source and chemical feedstock. A key element of lignin biosynthesis is unknown: how do lignin precursors (monolignols) get from inside the cell out to the cell wall where they are polymerized? Modeling indicates that monolignols can passively diffuse through lipid bilayers, but this has not been tested experimentally. We demonstrate significant monolignol diffusion occurs when laccases, which consume monolignols, are present on one side of the membrane. We hypothesize that lignin polymerization could deplete monomers in the wall, creating a concentration gradient driving monolignol diffusion. We developed a two-photon microscopy approach to visualize lignifying Arabidopsis thaliana root cells. Laccase mutants with reduced ability to form lignin polymer in the wall accumulated monolignols inside cells. In contrast, active transport inhibitors did not decrease lignin in the wall and scant intracellular phenolics were observed. Synthetic liposomes were engineered to encapsulate laccases, and monolignols crossed these pure lipid bilayers to form polymer within. A sink-driven diffusion mechanism explains why it has been difficult to identify genes encoding monolignol transporters and why the export of varied phenylpropanoids occurs without specificity. It also highlights an important role for cell wall oxidative enzymes in monolignol export. Abstract : The lignin polymerizing laccase enzymes in cell walls establish an energetically favorable concentration gradient that drives diffusion of lignin monomers from inside the cell to the wall outside.